Insect symbionts in food webs. - McLean, A; Parker, B; Hrček, J; Henry, L; Godfray, H (Royal Society, 2016)
Recent research has shown that the bacterial endosymbionts of insects are abundant and diverse, and that they have numerous different effects on their hosts’ biology. Here we explore how insect endosymbionts might affect the structure and dynamics of insect communities. Using the obligate and facultative symbionts of aphids as an example, we find that there are multiple ways that symbiont presence might affect food web structure. Many symbionts are now known to help their hosts escape or resist natural enemy attack, and others can allow their hosts to withstand abiotic stress or affect host plant use. In addition to the direct effect of symbionts on aphid phenotypes there may be indirect effects mediated through trophic and non-trophic community interactions. We believe that by using data from barcoding studies to identify bacterial symbionts, this extra, microbial dimension to insect food webs can be better elucidated.